T-cells play the classics with a different spin. - Dustin, M (American Society for Cell Biology, 2014)
The immune system uses much of the classic machinery of cell biology, but in ways that put a different spin on organization and function. Striking recent examples include the demonstration of intraflagellar transport protein and hedgehog contributions to the immune synapse, even though immune cells lack a primary cilium that would be the typical setting for this machinery. In a second example, lymphocytes have their own subfamily of integrins, the β2 subfamily, and only integrins in this family form a stable adhesion ring using freely mobile ligands, a key feature of the immunological synapse. Finally, we showed recently that T-cells use endosomal sorting complexes required for transport (ESCRTs) at the plasma membrane to generate T-cell antigen receptor-enriched microvesicles. It is unusual for the ESCRT pathway to operate at the plasma membrane, but this may allow a novel form of cell-cell communication by providing a multivalent ligand for major histocompatibility complex-peptide complexes and perhaps other receptors on the partnering B-cell. Immune cells are thus an exciting system for novel cell biology even with classical pathways that have been studied extensively in other cell types.